Single-isomer carboxymethyl-γ-cyclodextrin as chiral resolving agent for capillary electrophoresis - Benkovics, Gábor; Fejős, Ida; Darcsi, András; Varga, Erzsébet; Malanga, Milo; Fenyvesi, Éva; Sohajda, Tamás; Szente, Lajos; Béni, Szabolcs; Szemán, Julianna (Journal of chromatography. A, Including electrophoresis and other separation methods, 2016)
Herein we report on the synthesis, characterization and the novel capillary electrophoretic use of octakis-(2,3-di-O-methyl-6-O-carboxymethyl)-γ-cyclodextrin sodium salt (ODMCM). ODMCM is the first single-isomer carboxymethyl-γ-cyclodextrin that is fully methylated on its secondary side and carries ionizable carboxymethyl functions on its primary side. ODMCM was prepared with high isomeric purity through a four-step synthetic procedure. The purity of each intermediate was characterized by appropriate chromatographic methods, while the isomeric purity of the carboxymethylated product was determined by an HPLC method using a CD-Screen-IEC column and by a capillary electrophoretic method using indirect UV detection, as well. The structural identification of the ODMCM was carried out by 1D, 2D NMR spectroscopy and ESI-MS. The acid-base characterization of the chiral selector was carried out by (1)H NMR-pH titration. The chiral separation ability of the synthesized selector was studied by chiral capillary electrophoresis. ODMCM was used as a background electrolyte additive to separate enantiomers of representative pharmacologically significant model molecules such as propranolol, citalopram, ketamine, tapentadol and dapoxetine. The effects of the selector concentration and the pH of the background electrolyte on the enantiorecognition properties were investigated. (1)H NMR spectroscopy was further applied to get deeper insight of the host-guest inclusion complex formation. The pH-dependent enantioselectivity of this new single-isomer chiral selector was demonstrated by chiral capillary electrophoresis and (1)H NMR spectroscopy.
Keywords: gama-cyklodextriny; stereoizomerie; indikátory a reagencie; Magnetic Resonance Spectroscopy; Stereoisomerism; Hydrogen-Ion Concentration; Indicators and Reagents; Spectrophotometry, Ultraviolet; Electrophoresis, Capillary; hmotnostní spektrometrie s elektrosprejovou ionizací; Chromatography, High Pressure Liquid; elektroforéza kapilární; gamma-Cyclodextrins; magnetická rezonanční spektroskopie; Spectrometry, Mass, Electrospray Ionization; vysokoúčinná kapalinová chromatografie; spektrofotometrie ultrafialová; koncentrace vodíkových iontů